Expression of circulating oar-miR-485-5p and oar-miR-493-5p during the estrous cycle and early pregnancy in ovine plasma - Ucar, Eyyup Hakan; Hitit, Mustafa; Kose, Mehmet; Atli, Mehmet Osman (FapUNIFESP (SciELO), 2024)
In the current study, we aimed to assess the expression levels of two circulating microRNAs (miRNA) (oar-miR-485-5p and oar-miR-493-5p) in the ovine plasma during the peri-implantation. After mating, we collected the plasma samples from a total of 8 ewes on day 22 of pregnancy (P22; n = 4) and day 22 of the estrous cycle (C22; n=4). We used mature miRNA sequences for oar-miR-485-5p and oar-miR-493-5p out of one hundred fifty, which were retrieved from our microarray results of previous study. We showed that the miRNA expression of oar-miR-485-5p and oar-miR-493-5p were upregulated in P22 (P<0.05) when compared to C22. Those two miRNAs targeted 311 target genes in the peri-implantation period of pregnancy. Furthermore, we revealed 151 GO/pathway terms in biological process (BP) and 25 GO/pathway terms in molecular function (MF), while we demonstrated 13 GO/pathway terms in cellular component (CC). We revealed three hub genes as interleukin 2 (IL2), interleukin 18 (IL18), and C-X-C Motif Chemokine Ligand 10 (CXCL10). In conclusion, both miR-485-5p and oar-miR-493-5p have the potential to be a biomarker to understand peri-implantation of the ovine pregnancy in the aspect of pregnancy-reflected changes in maternal plasma.
Keywords: Plasma; Oar-Mir-493-5p; Original Article; Oar-Mir-485-5p; Microrna; Ovine